Nephrolithiasis in ankylosing spondylitis and its relationship with disease assessment scales - REZVANİ, AYLİN; REZVANİ, AYLİN; Aktas, Ilknur; TAŞTEKİN, NURETTİN; Celiker, Reyhan; SARIKAYA, SELDA; DURSUN, ERBİL; ÖZDOLAP, ŞENAY; DURSUN, NİGAR; ZATERİ, COŞKUN; ALTAN İNCEOĞLU, LALE; BİRTANE, MURAT; et al. (My University, 2019)
OBJECTIVE: The aim of this study was to investigate the frequency of renal calculi in patients with ankylosing spondylitis (AS) and to determine its relationship with disease assessment variables.